Analysis of the Utilization of TikTok Content as a Coping Strategy to Reduce Stress Among Final-Year Students Using a Classification Method - Husna Karima; Zulfadhilah, Muhammad; Prastya, Septyan Eka; Pratiwi, Evi Lestari (INSTALL: Information System and Technology Journal, 2025)
Stress represents a prevalent psychological challenge among final- year university students, particularly during thesis completion. Academic pressure, social demands, and future uncertainty trigger stress that negatively impacts mental health. Social media, especially TikTok, is increasingly utilized as a coping mechanism to reduce stress through entertainment, educational, and motivational content. This study aims to analyze TikTok content utilization as a coping strategy for stress reduction among final-year students using a classification method. This quantitative research employed a survey approach with a population of 342 active TikTok users among final- year students at Sari Mulia University. Data were collected through an online questionnaire covering variables including content type, duration, features used, and psychological indicators such as anxiety, emotions, escapism, and coping effectiveness. Data preprocessing included one-hot encoding, SMOTE, and normalization, followed by classification using Support Vector Machine with RBF kernel optimized through GridSearchCV. Results revealed very high correlations among psychological variables (r ≈ 0.93–1.00), while correlations between content type and stress reduction were relatively low (0.00–0.15). Some pure entertainment content showed negative correlations with psychological improvement. The SVM model achieved high classification accuracy of approximately 94%. This study demonstrates that TikTok can serve as a short-term stress coping tool for final-year students, though its effectiveness depends heavily on the type of content consumed. Educational and motivational content shows greater potential for stress reduction compared to pure entertainment content. This research contributes to understanding digital mental health support mechanisms and provides insights for developing healthier media consumption strategies among university students.